Qualitative Exploration of Factors Making Physics Challenging for Students - Nurjanah, Siti; Martaputri, Nurul Aulia; Hulu, Hepi Kharisda; Novieyanti, Armelya; Aniasari, Yuri; Rashid, Salman (Jurnal Pembelajaran Fisika, 2024)
The majority of students tend to perceive physics as a challenging subject. While numerous studies have investigated the factors contributing to this challenge, more comprehensive qualitative research needs to be conducted that delves deeply into this phenomenon, particularly within the constructivist paradigm. This study employs the constructivist paradigm as a framework to examine the elements that contribute to students’ perception of physics as a challenging subject. This study employed a descriptive qualitative method. The data for this study were collected through a thematic analysis of comments from the Quora platform. The sample consisted of ten comments from the Quora website, selected based on the highest recommendations. The data were subjected to a thematic analysis using ATLAS.ti software version 9. The study identified seven primary themes that analyze the elements contributing to the challenges in acquiring knowledge in the field of physics. These topics include the nature of physics itself, the role of teachers, the characteristics of students, the disparity between physicists and non-experts, the curriculum, parental influence, and the discipline’s historical development. The challenges encountered in studying physics arise from intricate and interconnected causes. Further research could be undertaken to examine efficient learning strategies to overcome these challenges and explore additional variables that may contribute to this phenomenon.Keywords: Constructivist paradigm, physics challenges, physics education, student perceptions, thematic analysisDOI: http://dx.doi.org/10.23960/jpf.v12.n2.202401